Chemopreventive and therapeutic potential of chrysin in cancer: mechanistic perspectives. Issue 2 (4th March 2015) - Kasala, Eshvendar Reddy; Bodduluru, Lakshmi Narendra; Madana, Rajaram Mohanrao; V, Athira K.; Gogoi, Ranadeep; Barua, Chandana C
Highlights Short account on role of chrysin in multistep carcinogenesis process. Chemopreventive and therapeutic studies of chrysin in cell lines and animal models. Succinct description of mechanistic perspectives of chrysin. A colossal narration of effect of chrysin on signalling pathways and molecular targets. Brief note on pharmacokinetics of chrysin.